Self‐Calibrating Wave‐Encoded Variable‐Density Single‐Shot Fast Spin Echo Imaging - Chen, Feiyu; Taviani, Valentina; Tamir, Jonathan I.; Cheng, Joseph Y.; Zhang, Tao; Song, Qiong; Hargreaves, Brian A.; Pauly, John M.; Vasanawala, Shreyas S. (Journal of magnetic resonance imaging, 2018)
Background It is highly desirable in clinical abdominal MR scans to accelerate single‐shot fast spin echo (SSFSE) imaging and reduce blurring due to T2 decay and partial‐Fourier acquisition. Purpose To develop and investigate the clinical feasibility of wave‐encoded variable‐density SSFSE imaging for improved image quality and scan time reduction. Study Type Prospective controlled clinical trial. Subjects With Institutional Review Board approval and informed consent, the proposed method was assessed on 20 consecutive adult patients (10 male, 10 female, range, 24–84 years). Field Strength/Sequence A wave‐encoded variable‐density SSFSE sequence was developed for clinical 3.0T abdominal scans to enable high acceleration (3.5×) with full‐Fourier acquisitions by: 1) introducing wave encoding with self‐refocusing gradient waveforms to improve acquisition efficiency; 2) developing self‐calibrated estimation of wave‐encoding point‐spread function and coil sensitivity to improve motion robustness; and 3) incorporating a parallel imaging and compressed sensing reconstruction to reconstruct highly accelerated datasets. Assessment Image quality was compared pairwise with standard Cartesian acquisition independently and blindly by two radiologists on a scale from –2 to 2 for noise, contrast, confidence, sharpness, and artifacts. The average ratio of scan time between these two approaches was also compared. Statistical Tests A Wilcoxon signed‐rank tests with a P value under 0.05 considered statistically significant. Results Wave‐encoded variable‐density SSFSE significantly reduced the perceived noise level and improved the sharpness of the abdominal wall and the kidneys compared with standard acquisition (mean scores 0.8, 1.2, and 0.8, respectively, P < 0.003). No significant difference was observed in relation to other features (P = 0.11). An average of 21% decrease in scan time was achieved using the proposed method. Data Conclusion Wave‐encoded variable‐density sampling SSFSE achieves improved image quality with clinically relevant echo time and reduced scan time, thus providing a fast and robust approach for clinical SSFSE imaging. Level of Evidence: 1 Technical Efficacy: Stage 6 J. Magn. Reson. Imaging 2018;47:954–966.